Diabetes as a predictor of COVID-19 preventive behaviors - Gonzalez Casanova, Ines; Klingensmith, Rachel; Myers, Barbara A.; Anwar, Farrah; de Groot, Mary (Frontiers in Psychology, 2025)
IntroductionWe explored if diabetes status predicted differences in behavioral pathways associated with staying home at the beginning of the coronavirus-19 infectious disease (COVID-19), wearing a mask, and vaccinating in a convenience sample of US adults over a 12-month period of the COVID-19 pandemic (from May 2020 through June 2021).MethodsWe included participants who completed web-based surveys in May–June, 2020 (baseline), and at the 6-, 9-, 11- and 12- months follow-ups (n = 966). We collected information on demographic characteristics (baseline) and surveys with Likert-scale type questions to assess Health Beliefs Model and Theory of Planned Behavior constructs related to staying home (6-month), wearing masks in public spaces (9-month), and receiving the COVID-19 vaccine (11- and 12- month). Structural equation modeling was conducted to assess behavioral pathways and direct and indirect associations with diabetes.ResultsConstructs of the Theory of Planned Behavior and the Health Beliefs Model explained intention to stay home, to wear a mask, to vaccinate, and COVID-19 vaccination status. Diabetes status predicted intention to stay home directly (β = 0.21, p < 0.05) and indirectly through perceived severity (β = 0.11, p < 0.01). Overall, diabetes status was not associated with intention to wear a mask or vaccination.ConclusionFindings from this study highlight relevant pathways that can be leveraged to promote preventive behaviors in people with diabetes.